Hubungan nilai masyarakat & pembangunan: satu analisa - Zurina Mahadi,; Sino, Hukil (Universiti Kebangsaan Malaysia, 2007)
This review analyses the relevance of basic social values to the contemporary goals of national development. Shifting of development paradigm in Asia recognised the emerging concept of endogenous development with Japan as the prominent model. The relationship between values and development in general terms and specific dimensions of values as relevant to development were analysed from the perspectives of USA, Holland and different Asian countries including Malaysia